2020
DOI: 10.32536/jrki.v4i2.128
|View full text |Cite
|
Sign up to set email alerts
|

Analisis percepatan penyembuhan luka pada ibu post sectio sesarea multipara dengan pemberian olahan nanas (ananas comosus (l.merr) comosus)

Abstract: Latar belakang: Luka section sesarea merupakan pembedahan pada dinding uterus melalui perut di sebabkan beberapa indikasi medis yaitu placenta previa, preeklamsia, gawat janin, kelainan letak janin dan janin besar . Hal ini menimbulkan ketidak nyamanan pada ibu post partum. Olahan nanas mengandung enzim bromelain yang bermanfaat untuk anti-inflamasi yang dapat mempercepat pemulihan saat terjadi luka atau peradangan serta Kandungan vitamin C yang tinggi dapat mempercepat proses penyembuhan pada tubuh . Vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The characteristics of respondents based on parity in this study in the most experimental groups were multigravida, namely 8 people (73.3%), Primigravida 6 orang (40%), grande multipara 1 person (13.3%), and in the control group the most respondents in multigravida, namely 9 people (73.3%). The provision of processed pineapple (Ananas Comosus) to multipara mothers has the effect of helping the wound healing process due to bromelain enzymes and enzymes contained in pineapple fruit (Saleng, Sampara, Sudirman, 2020). Saleng et al (2020) concluded that the provision of processed pineapple (Ananas Comosus) to multipara mothers has an effect on the wound healing process due to bromelain enzymes contained in pineapples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of respondents based on parity in this study in the most experimental groups were multigravida, namely 8 people (73.3%), Primigravida 6 orang (40%), grande multipara 1 person (13.3%), and in the control group the most respondents in multigravida, namely 9 people (73.3%). The provision of processed pineapple (Ananas Comosus) to multipara mothers has the effect of helping the wound healing process due to bromelain enzymes and enzymes contained in pineapple fruit (Saleng, Sampara, Sudirman, 2020). Saleng et al (2020) concluded that the provision of processed pineapple (Ananas Comosus) to multipara mothers has an effect on the wound healing process due to bromelain enzymes contained in pineapples.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of processed pineapple (Ananas Comosus) to multipara mothers has the effect of helping the wound healing process due to bromelain enzymes and enzymes contained in pineapple fruit (Saleng, Sampara, Sudirman, 2020). Saleng et al (2020) concluded that the provision of processed pineapple (Ananas Comosus) to multipara mothers has an effect on the wound healing process due to bromelain enzymes contained in pineapples. The provision of processed pineapple (Ananas comosus) in multipara mothers has the effect of helping the wound healing process due to bromelain enzymes and enzymes contained in pineapples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The puerperium tends to be related to the process of returning the mother's body to its pre-pregnancy condition, and many of these processes are related to the process of uterine involution, accompanied by healing at the placenta (extensive wounds) including ischemia and autolysis. 10 The success of such resolutions is critical to maternal health, but apart from nutrition there are other factors such as the hygiene and lifestyle of each of these individuals.…”
Section: Introductionmentioning
confidence: 99%